The Management of Hisbah (Accountability) in the Crisis of Bankruptcy in Islamic Economic Law - Muhammad Sadeqi; Sobhan Abbaspour (آموزه‌‌های فقه مدني, 2021)
From the point of view that the crisis of bankruptcy entails to consider all economic and managerial aspects it should be managed far from the boundaries of the private law and bankruptcy law. For the bankruptcy private laws in most cases have been legislated in order to preserve the rights of creditors and less it refers to support business activities. However, the legal systems according to their priorities have dealt with the matter and create regulations. The theory of Islamic economic law for directing this crisis can be assessed based on the hisbah (Arabic: حسبة‎ accountability) and analyzed its functions in this regard. In the present paper for evaluating the inclusion of bankruptcy under the hisbah matters, it has studied the sides of this issue and besides, the efficiency of hisbah matters for controlling the crisis of bankruptcy it presents its challenges. With respect to this, it seems that in Islamic economic law far from preserving the private right of creditors, it can be imagined mechanisms for company (firm)-centric and supporting debtor through the hisbah way with considering its characteristics, isolation from the pro-creditor approach, which have a significant impact on reviving the bankrupted and keeping the companies. In other words, in Islamic law in proportion to have common public -private validity, hisbah matters have several tools for managing the crisis of bankruptcy. The alternative and protective methods such as borrowing, dispute resolution, qardh al-hasan (Arabic: القرض الحسن lending with no interest), Bayt al-Mal (Arabic: بیت‌المال literally: house of money, meaning: the “fiscus” or “treasury” of the Muslim government), mortgage, collateral -surety-, respite or assignment of contract are of these tools.